Remobilization of sucrose from the culm during germination of sugarcane setts - Boussiengui-Boussiengui, Gino (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2005.